Penerapan Model Pembelajaran Pemecahan Masalah Double Loop un-tuk Meningkatkan Hasil Belajar Matematika pada Siswa SMP Kelas VIII: Implementing the Double Loop Problem-Solving Learning Model to Improve Mathematics Learning Outcomes in Eighth-Grade Students - Rafaini, Rafaini; Ramlan, Andi Mariani; Halidin, Halidin (Journal of Research in Science and Mathematics Education, 2025)
Purpose: This study aimed to improve the mathematical learning outcomes of eighth-grade students at Negeri 14 Central Buton by applying the Double Loop Problem-Solving learning model. Methodology: This study employed a Classroom Action Research (CAR) approach, conducted in collaboration between teachers and researchers. The research followed a structured procedure, including planning, implementation, observation, and reflection. The study was carried out in two cycles. Data collected included both quantitative data from learning outcome tests and qualitative data from observation sheets. The research hypothesis proposed that applying the Double Loop Problem-Solving learning model would improve the mathematics learning outcomes of students in class VIIIB at SMPN 14 Central Buton. The study involved 21 students, comprising 11 boys and 10 girls. The results were evaluated based on the Minimum Completeness Criteria, set at 65. Findings: Based on the results of the first cycle test, the average score was 68.25, with a classical completeness rate of 61.90%. In the second cycle test, the average score increased to 78.93, with a classical completeness rate of 85.71%. This indicates an improvement in student performance from the first to the second cycle. Significance: Based on the student learning outcomes described above, it can be concluded that the Double Loop Problem-Solving learning model can enhance the mathematics learning outcomes of students in Class VIII at SMP Negeri 14 Central Buton.